The Political Movement of The Unity of Ulama Throughout Aceh (Pusa) and Its Implications on Social and Political Life in Aceh 1939-1962 - Jergian Jodi; Septian Fatianda; Randi Stiawan (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
The All Aceh Ulama Association (PUSA) is where reformist clerics from Aceh gather. PUSA was born based on their concerns about the socio-religious conditions in Aceh, which were trapped in rigid Islamic practices, so there had to be a breakthrough to change the education system in Aceh to make it more advanced. Since the first PUSA congress in 1940, this organization began to serve as a forum for conveying people's aspirations so that PUSA was actively involved in a series of political events in Aceh. The written discussion focuses on the period from 1939, the year of PUSA's formation, until 1962, the end of PUSA's political influence. This research is a social history study, so a socio-political approach is used to analyze the PUSA political movement. Meanwhile, the four method steps in research are heuristics, verification, interpretation, and historiography. The research results show that the political action carried out by PUSA aims to fight for Aceh to be free from all forms of colonialism and to implement Islamic Sharia. Some forms of PUSA political movements include holding a congress in Sigli, diplomacy with Japan, carrying out a rebellion against the Dutch, eradicating feudal practices and uleebalang power, and fighting for Aceh's rights in national politics in the DI/TII rebellion.